Inactivation of tomato WAT1 leads to reduced susceptibility to Clavibacter michiganensis through downregulation of bacterial virulence factors - Koseoglou, Eleni; Hanika, Katharina; Mohd Nadzir, Mas M.; Kohlen, Wouter; van der Wolf, Jan M.; Visser, Richard G. F.; Bai, Yuling (Frontiers in Plant Science, 2023)
Tomato bacterial canker caused by Clavibacter michiganensis (Cm) is considered to be one of the most destructive bacterial diseases of tomato. To date, no resistance to the pathogen has been identified. While several molecular studies have identified (Cm) bacterial factors involved in disease development, the plant genes and mechanisms associated with susceptibility of tomato to the bacterium remain largely unknown. Here, we show for the first time that tomato gene SlWAT1 is a susceptibility gene to Cm. We inactivated the gene SlWAT1 through RNAi and CRISPR/Cas9 to study changes in tomato susceptibility to Cm. Furthermore, we analysed the role of the gene in the molecular interaction with the pathogen. Our findings demonstrate that SlWAT1 functions as an S gene to genetically diverse Cm strains. Inactivation of SlWAT1 reduced free auxin contents and ethylene synthesis in tomato stems and suppressed the expression of specific bacterial virulence factors. However, CRISPR/Cas9 slwat1 mutants exhibited severe growth defects. The observed reduced susceptibility is possibly a result of downregulation of bacterial virulence factors and reduced auxin contents in transgenic plants. This shows that inactivation of an S gene may affect the expression of bacterial virulence factors.